2012
DOI: 10.1111/j.1479-8425.2012.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Measure of sleep and physical activity by a single accelerometer: Can a waist-worn Actigraph adequately measure sleep in children?

Abstract: Accelerometers could potentially be used to assess physical activity and sleep using the same monitor; however, two different positions are typically used for the assessment of physical activity and sleep (waist and wrist, respectively). The aim of this study is to evaluate the concordance between wrist‐ and waist‐worn Actigraphs for sleep scoring using existing algorithms developed for placement on the wrist. Sixty‐two Danish children aged 10.3 ± 0.6 years (mean ± standard deviation) wore an accelerometer (Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 23 publications
8
82
0
Order By: Relevance
“…Although Actigraph has developed an algorithm to scale wrist-worn data to hip-worn estimations, there is little evidence currently available to support valid estimation of physical activity using the GT3Xþ when worn on the wrist. Moreover, a recent study using the Actigraph in children has found, for sleep estimation, that wrist and hip placements are not interchangeable (Hjorth et al, 2012). One important contribution of the present study is that a wrist-worn GT3Xþ is reliable and valid to measure sleep.…”
Section: Discussionmentioning
confidence: 79%
“…Although Actigraph has developed an algorithm to scale wrist-worn data to hip-worn estimations, there is little evidence currently available to support valid estimation of physical activity using the GT3Xþ when worn on the wrist. Moreover, a recent study using the Actigraph in children has found, for sleep estimation, that wrist and hip placements are not interchangeable (Hjorth et al, 2012). One important contribution of the present study is that a wrist-worn GT3Xþ is reliable and valid to measure sleep.…”
Section: Discussionmentioning
confidence: 79%
“…As such, we reliably examined the association between sleep and weight status. 34 In contrast, Araujo et al examined self-reported sleep duration at age 13 on BMI at ages 13 and 17 and only found cross-sectional associations. 20 Self-reported sleep may be an adequate measure of sleep for cross-sectional investigations, but may be inadequate for examining sleep longitudinally.…”
Section: Discussionmentioning
confidence: 97%
“…The GT3X? uses a validated algorithm that allows researchers who use a 24 h waist-worn accelerometry protocol to distinguish children's nocturnal sleep (including night time wake episodes) from day time activities (Barreira et al 2014;Hjorth et al 2012).…”
Section: Methodsmentioning
confidence: 99%